Role of Country Governance for Improved Environmental Performance - Tze San Ong; Wei Ni Soh; Chee Leong Tan; Boon Heng Teh; Tze Chin Ong (Universitas Pasundan, 2022)
Environmental issues are gaining significant attention at the organizational and country levels because of the growing pollution and greenhouse gas emissions. This study aimed to examine the relationship between country governance (CG) and environmental protection (EP) at the country level. In addition, the study further examined the outcome of EP in developing and developed countries. Neoliberal environmental governance theory was used as an underpinning theory. The data for CG were obtained from the Worldwide Governance Indicators and Environmental Performance Index for the period between 2006 and 2016. Two control variables, namely, Primary School Enrollment and Country Population, were also considered. The panel regression model was used for data analysis. The findings revealed that CG had a significant relationship with EP. Considering that governments have the power to foster governance practices, companies are prompted to enhance their governance performance, invariably leading to greater engagement in sustainability by improving their regulatory environment and enforcement mechanisms. The findings of the study will assist policymakers and decision-makers in setting priorities for the government to achieve sustainable development goals.